Long Chain Alcohols Produced by Trichoderma citrinoviride Have Phagodeterrent Activity against the Bird Cherry-Oat Aphid Rhopalosiphum padi - Ganassi, Sonia; Grazioso, Pasqualina; De Cristofaro, Antonio; Fiorentini, Fabio; Sabatini, Maria Agnese; Evidente, Antonio; Altomare, Claudio (Frontiers in Microbiology, 2016)
In this study we report the effects of fungal metabolites isolated from cultures of the fungus Trichoderma citrinoviride ITEM 4484 on the feeding preference of the aphid Rhopalosiphum padi, a major pest of cereal crops. Different phagodeterrent metabolites were purified by a combination of direct and reverse phase column chromatography and thin-layer chromatography. Chemical investigations, by spectroscopic and chemical methods, led to the identification of different long chain primary alcohols (LCOHs) of the general formula R-OH, wherein R is a long, unbranched, unsubstituted, linear aliphatic group. LCOHs have been reported as components of lepidopteran pheromone blends, but their phagodeterrent effect to aphids is herein reported for the first time. The effects of LCOHs on R. padi were studied by behavioral and electrophysiological bioassays. Feeding preference tests that were carried out with winged and wingless morphs of R. padi showed that LCOHs had high phagodeterrent activity and restrained aphids from settling on treated leaves at a concentration as low as 0.15 mM (0.036 g/l). The results of different electrophysiological analyses indicated that taste receptor neurons located on the aphid tarsomeres were involved in the LCOHs perception. Behavioral assays carried out with some commercial agrochemicals, including azadirachtin A, pyrethrum and a mineral oil-based product, in combination with 1-hexadecanol, the LCOH most abundantly produced by T. citrinoviride ITEM 4484, showed that these different active principles could be applied together, resulting in a useful increase of the phagodeterrent effect. The data shown indicate that these compounds can be profitably utilized for novel applications in biotechnical control of aphid pests. Furthermore, the tested LCOHs have no chiral centers and therefore can be obtained with good yield and at low cost through chemical synthesis, as well as from natural sources.